Study on wear in spur gears based on an improved load distribution model considering the effects of corner contact. (September 2020) - Chen, Zhiying; Ji, Pengfei
Highlights: The effects of corner contact have a significant influence on wear depth and LSTE. Wear can make the load share ratio and transmission error become time-varying. The time-varying correlation between wear and mesh characteristics is confirmed. Gear ratio and modulus can obviously influence meshing characteristics and wear. Abstract: Gear surface wear is an unavoidable tooth profile deviation and can influence gear load distribution and transmission error. Because of that, it is necessary to study the interaction between them and wear. For that purpose, a modified wear prediction model has been established by combining the potential energy method, and an improved load distribution model considering the effect of corner contact. The load share ratio (LSR) obtained from the improved model is verified by the finite element method (FEM). And relative to the FEM, the proposed model is much more efficient. Besides, the influences of wear accumulation process and corner contact on loaded static transmission error (LSTE) and load distribution are discussed. The results show that considering the effect of corner contact is necessary and can improve the accuracy of the wear prediction. And, it can be observed that there is a significant time-varying characteristic on LSTE, LSR of worn gear, as well as a correlation between them. Furthermore, the influence of gear modulus and gear ratio is discussed as well and it is found that both can effectively reduce the wear depth and significantly influence the condition of corner contact.